Time Lag Between Light and Heat Diurnal Cycles Modulates CIRCADIAN CLOCK ASSOCIATION 1 Rhythm and Growth in Arabidopsis thaliana - Masuda, Kosaku; Yamada, Tatsuya; Kagawa, Yuya; Fukuda, Hirokazu (Frontiers in Plant Science, 2021)
Plant growth responses to cues such as light, temperature, and humidity, enable the entrainment of the circadian rhythms with diurnal cycles. For example, the temperature variations between day and night affect plant growth and accompany the time lag to light cycle. Despite its importance, there has been no systematic investigation into time lags, and the mechanisms behind the entrainment of the circadian rhythms with multiple cycles remains unknown. Here, we investigated systemically the effects of the time lag on the circadian rhythm and growth in Arabidopsis thaliana. To investigate the entrainment status of the circadian clock, the rhythm of the clock gene CIRCADIAN CLOCK ASSOCIATION 1 (CCA1) was measured with a luciferase-reporter assay. As a result, the rhythm was significantly modulated by the time lag with +10 C heating for 4 h every day but not −10 C cooling. A model based on coupled cellular oscillators successfully described these rhythm modulations. In addition, seedling growth depended on the time lag of the heating cycle but not that of the cooling cycle. Based on the relationship between the CCA1 rhythms and growth, we established an estimation method for the effects of the time lag. Our results found that plant growth relates to the CCA1 rhythm and provides a method by which to estimate the appropriate combination of light-dark and temperature cycles.